2007
DOI: 10.1634/stemcells.2006-0106
|View full text |Cite
|
Sign up to set email alerts
|

A Cassette System to Study Embryonic Stem Cell Differentiation by Inducible RNA Interference

Abstract: Although differentiation of pluripotent embryonic stem cells is restricted by a hierarchy of transcription factors, little is known about whether post-transcriptional mechanisms similarly regulate early embryoid differentiation. We developed a system where small hairpin (sh)RNAs can be induced in embryonic stem (ES) cells from a defined locus following integration by Flp recombinase-mediated DNA recombination. To verify the system, the key transcription factor Stat3, which maintains pluripotency, was downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For example, a previous study showed that siRNA inhibition of ZFP36L1 expression in mouse myoblasts inhibits cell differentiation 58. However, a different investigation showed that induction of shRNA specific for ZFP36L1 strongly stimulates cardiomyocyte formation within embryoid bodies 59. In contrast, ZFP36L2 knockdown promoted adipogenesis compared with the shRNA control, indicating that TTP family proteins might target different mRNAs and play different functional roles under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study showed that siRNA inhibition of ZFP36L1 expression in mouse myoblasts inhibits cell differentiation 58. However, a different investigation showed that induction of shRNA specific for ZFP36L1 strongly stimulates cardiomyocyte formation within embryoid bodies 59. In contrast, ZFP36L2 knockdown promoted adipogenesis compared with the shRNA control, indicating that TTP family proteins might target different mRNAs and play different functional roles under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…When ectopically expressed TIS11b promoted myeloid progenitor L-G cell proliferation and inhibited differentiation [62]. Intriguingly, siRNA mediated TIS11b knockdown in murine embryonic stem cells promoted their differentiation to cardiomyocytes [106]. Increased expression of TIS11b was reported in primary breast tumours [107] and hepatocellular carcinomas [108].…”
Section: Tis11 Family In Cell Functions and Diseasementioning
confidence: 99%
“…Inducible RNAi raises the prospect of temporal and dosage-sensitive control over the induction of gene knockdown. Previously reported strategies for inducible RNAi in ES cells or transgenic mice include the use of tamoxifen-inducible Cre-recombinase to activate vector-based shRNAs and shRNAs integrated in a defined locus (10,11), as well as the use of a doxycyclineinducible shRNA cassette integrated in a defined locus (12,13). Here we describe an alternative drug-inducible system based on the Ainv15 ES cell line, in which an shRNA-mir cassette is directed to the constitutively active hypoxanthine-guanine phosphoribosyltransferase (HPRT) locus upon Cre-mediated sitespecific recombination.…”
Section: Rnai Is a Powerful Tool For Interrogating Gene Function In Ementioning
confidence: 99%